"Free replacement extended warranty" or "traditional extended warranty": Optimal extended warranty selection strategy. (25th February 2022) - Cao, Kaiying; Su, Yunyi; Xu, Yuqiu; Wang, Jia
Abstract : A variety of new extended warranty services are increasingly emerging nowadays, among which "free replacement extended warranty" service is favored by many consumers. Considering resource constraints and cannibalism, firms are facing the challenge of providing the "free replacement extended warranty" service (NR) or the "traditional extended warranty" service (EW). To meet this challenge, we develop theoretical models and optimize the models to obtain management implications. The results show that firms should choose the NR strategy when the traditional extended warranty cost coefficient is relatively high and the free replacement cost coefficient is relatively low. Otherwise, the EW strategy is better.